Anticipatory responses to offensive actions in boxing - Akopyan, A. O. (Theory and Practice of Physical Culture, 2017)
Abstract: Individual anticipatory abilities to counter the opponent`s offensive actions in boxing bouts have always been highly appreciated in boxing. Subject to our study were 16 elite boxers of middle-weight categories (60-75 kg) aged 22±2.3 years. The following methods were used in the study: NeuroSoft Psycho-test system to classify the subjects by the psychological types; and a special punch training system to rate the visual-motor responses. The study data and analyses were used to determine the athletes` psychological types, rate the visual-motor responses and manifestations of their anticipatory responses.